A6.7 The junctional adhesion molecule JAM-3 regulates the motility of fibroblast-like synoviocytes. (13th February 2015) - König, U; Heitzmann, M; Beckmann, D; Hillen, J; Hansen, U; Saunders, U; Hartmann, C; Korb-Pap, A; Pap, T
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a disease of a continuous activation and expansion of the synovium involving migration and dissemination of fibroblast-like synoviocytes (FLS). Several lines of evidence indicate that adhesion molecules play a crucial role in this process. We have focused on the junctional adhesion molecule 3 (JAM-3), known to be involved in adhesion, polarity and migration of other cells. So far it has been demonstrated that blocking of JAM-3 in a serum transfer model of RA ameliorates the disease. However, the question of whether JAM-3 is involved in fibroblast motility or primarily regulates the influx of inflammatory cells remains unknown. Therefore, our objective was to clarify the involvement of JAM-3 in the establishment of cell-cell and cell-matrix contacts as well as in the migration of FLS. Materials and methods: As an arthritis model we use human TNFalpha transgenic (hTNFtg) mice that due to high levels of human TNFalpha develop a RA-like disease. FLS form these animals as well as form JAM-3 floxed mice CreERT2 (tamoxifen inducible cre line) and control mice were isolated by collagenase digestion of the hind paws. Cells were subjected to electrical cell-substrate impedance sensing (ECIS) surface staining (FACS), immunofluorescence, in vitro cell migration assays and standard molecular biology methods. Results: JAM-3 was found on both wild type and hTNFtg synoviocytes. Blocking or silencing of JAM-3 significantly increased cell spreading in an modified scratch assay but decreased migration in an in vitro transmigration assay, indicating that JAM-3 is involved in the establishment of cell-cell contacts between FLS. In line with this notion ECIS experiments revealed altered adhesion properties of these cells. Explaining these findings, we found that JAM-3 co-localises with the tight junction molecule zo-1 at cell contact sites, which are connected to actin cell filaments. The ultrastructure of these structures and an influence of Jam-3 on the cytoskeleton dynamics is under investigation. Conclusions: JAM-3 modulates migration of FLS in vitro, which may contribute to the beneficial effects of JAM-3 inhibition as seen in the serum transfer model of RA in vivo . We suggest that Jam-3 is an adhesion molecule, responsible for controlling motility by organising the cytoskeleton in FLS.